Icons and idiots straight talk on leadership - Lutz, Robert A. (Blackstone, 2013)
When Bob Lutz retired from General Motors in 2010, after an unparalleled forty-seven-year career in the auto industry, he was one of the most respected leaders in American business. He had survived all kinds of managers over those decades: tough and timid, analytical and irrational, charismatic and antisocial, and some who seemed to shift frequently among all those traits. His experiences made him an expert on leadership, every bit as much as he was an expert on cars and trucks.
Keywords: Leadership -Case studies